Adaptation, Clonal Interference, and Frequency-Dependent Interactions in a Long-Term Evolution Experiment with Escherichia coli. Issue 2 (24th April 2015) - Maddamsetti, Rohan; Lenski, Richard E; Barrick, Jeffrey E
Abstract: Twelve replicate populations of Escherichia coli have been evolving in the laboratory for >25 years and 60, 000 generations. We analyzed bacteria from whole-population samples frozen every 500 generations through 20, 000 generations for one well-studied population, called Ara−1. By tracking 42 known mutations in these samples, we reconstructed the history of this population's genotypic evolution over this period. The evolutionary dynamics of Ara−1 show strong evidence of selective sweeps as well as clonal interference between competing lineages bearing different beneficial mutations. In some cases, sets of several mutations approached fixation simultaneously, often conveying no information about their order of origination; we present several possible explanations for the existence of these mutational cohorts. Against a backdrop of rapid selective sweeps both earlier and later, two genetically diverged clades coexisted for >6000 generations before one went extinct. In that time, many additional mutations arose in the clade that eventually prevailed. We show that the clades evolved a frequency-dependent interaction, which prevented the immediate competitive exclusion of either clade, but which collapsed as beneficial mutations accumulated in the clade that prevailed. Clonal interference and frequency dependence can occur even in the simplest microbial populations. Furthermore, frequency dependence may generate dynamics that extend the period of coexistence that would otherwise be sustained by clonal interference alone.